Evaluation of 10 cases of lyme disease presenting with erythema migrans in Istanbul, Turkey [Istanbul'da Eritema Migrans ile Başvuran 10 Lyme Olgusunun Deʇerlendirilmesi] - (:unkn) unknown (Ankara Microbiology Society, 2015)
Lyme disease (LD) is a tick-borne, multisystemic infection caused by Borrelia burgdorferi. Although variable rates of seropositivity for B.burgdorferi have been reported between 2% to 44% in Turkey, its actual prevalence is not well-understood. The aim of this retrospective study was to evaluate the characteristics of 10 cases of LD presenting as erythema migrans (EM) between 2009 and 2013 from Istanbul which is one of the metropolitan cities of Turkey. Of the patients, five were male and five were female, ages between 9-51 years (mean age: 34.5 years). Five of the patients were admitted in June, three in October, one in November and two in December and all have the history of tick bite in last 1 -2 weeks. There were no clinical symptoms for systemic infection among the patients with normal level routine laboratory test (whole blood count and biochemical tests) results. Five of the cases had EM lesions in the trunk, three in the upper extremities, and two in the lower extremities. Four patients presented with annular, three with solitary macular, and three with target-like EM lesions. In all cases, the biopsy specimens were positive for B.burgdorferi sensu lato DNA with polymerase chain reaction and all were also positive in terms of B.burgdorferi IgM antibodies with ELISA. Nine patients were treated with oral doxycycline, 100 mg twice daily and one child patient was treated with oral amoxicillin 500 mg twice daily for 21 days. EM lesions disappeared within 2-4 weeks in all patients. There was no clinical evidence for systemic involvement in any of the patients like neurologic, cardiac, and joint involvement at the follow-ups on the third, sixth and 12th months. To our best knowledge, 10 patients in this study are the largest EM series reported from Turkey. The increase in the number of LD cases may be associated with increased tick bite and increased awareness due to the emergence of concurrent Crimean-Congo hemorrhagic fever epidemic in Turkey. As a result, when enlarged erythematous lesions on the skin were observed, LH must also be considered in differential diagnosis, history of tick bite should be questioned and etiological diagnostic test should be performed.
Keywords: Borrelia burgdorferi; Erythema chronicum migrans; Lyme Disease; Turkey